The impact of risk willingness and opportunity recognition on business owners' performance in Sabah, Malaysia / Deewasnari Muddat ... [et al.] - Muddat, Deewasnari; Ambad, Sylvia Nabila Azwa; Mohd Roslin, Rosmimah; Lajuni, Nelson (Faculty of Business and Management, 2021)
This paper examines the impact of risk willingness and opportunity recognition on business owners' performance in Sabah, Malaysia. The paper adopts non-probability sampling, known as a purposive sampling method, in selecting business owners. A total of 600 surveys using self-conducted questionnaires structured on a 7-point Likert scale is distributed, and subsequently, 525 questionnaires are returned. The EAO dimensions assessed in the paper are risk willingness and opportunity recognition. Data collected are analysed using the SEM-PLS technique through the SmartPLS 3.3.2 software. The study found a positive effect of risk willingness and opportunity recognition on the business owners' performance. Accordingly, this paper's theoretical and practical implication supports some of the previous findings and arguments that EAO plays an essential role in influencing micro-business owners' performance.